Growth medium- and strain-dependent bactericidal efficacy of blue light against Shiga toxin-producing Escherichia coli on food-grade stainless steel and plastic. (May 2022) - Wu, Shuyan; Hadi, Joshua; Brightwell, Gale
Abstract: Shiga toxin-producing Escherichia coli (STEC) are a major group of human pathogens and may persist on both abiotic and biotic surfaces. In this report, two blue-light prototypes were used to evaluate the antimicrobial efficacy against STEC on food processing surfaces (stainless steel and polyoxymethylene plastic). Investigation using a light-bulb prototype (Prototype 1 at 405 nm, 26 mW/cm 2 ) showed significant antimicrobial effects in nutrient deficient condition but not in nutrient rich condition, demonstrating that the presence of organic matters from rich nutrient medium was thought to be light-absorptive and reduce the bactericidal efficacy of blue light, as evident from the lack of bacterial reduction when suspended in cooked meat broth. An advanced (surface-mounted-diode) light panel, Prototype 2 with high light intensity (405 nm; 50 mW/cm 2 ) was able to inactivate a cocktail of seven STEC strains (from seven major serotypes O26, O45, O103, O111, O121, O145 and O157) on type 304 stainless steel (1.66 log10  CFU) and polyoxymethylene plastic (4.25 log10  CFU) at light dosages of 720 and 45 J/cm 2, respectively when cells were illuminated in a nutrient-deficient medium (M9 broth). Post-treatment, no STEC cells were recoverable from plastic, both when tested on plates (agar or petrifilms) and by polymerase chain reaction (PCR). In contrast, surviving colonies were identified on samples taken from stainless steel, albeit only four strains could be detected by PCR analysis – those belonging to serotypes O26, O45, O103 and O157 – which indicated that the susceptibility of STEC to blue light varied across the tested strains. Highlights: The efficiency of applied blue light on stainless steel and on plastic was varied. Blue light at 405 nm could inactivate STEC below detection level on plastic. The presence of organic material reduced the efficiency of the blue light inactivation. The efficacy of blue-light inactivation (405 nm) of STEC was strain-specific.